Roadkill : a Cal Leandros novel - Thurman, Rob. (New York : Roc, 2010)
A gypsy comes to the Leandros brothers wanting them to find a stolen coffin that contains the Plague of the World.
Keywords: Leandros, Cal (Fictitious character) -- Fiction; Brothers -- Fiction; Plague -- Fiction; Supernatural -- Fiction; Romanies -- Fiction; Private investigators -- Fiction; Fantasy fiction